Loxapine inhibits replication of hepatitis A virus in vitro and in vivo by targeting viral protein 2C - Matsuda, Mami; Hirai-Yuki, Asuka; Kotani, Osamu; Kataoka, Michiyo; Zheng, Xin; Yamane, Daisuke; Yokoyama, Masaru; Ishii, Koji; Muramatsu, Masamichi; Suzuki, Ryosuke (PLoS pathogens, 2024)
No antiviral drugs currently are available for treatment of infection by hepatitis A virus (HAV), a causative agent of acute hepatitis, a potentially life-threatening disease. Chemical screening of a small-compound library using nanoluciferase-expressing HAV identified loxapine succinate, a selective dopamine receptor D2 antagonist, as a potent inhibitor of HAV propagation in vitro . Loxapine succinate did not inhibit viral entry nor internal ribosome entry site (IRES)-dependent translation, but exhibited strong inhibition of viral RNA replication. Blind passage of HAV in the presence of loxapine succinate resulted in the accumulation of viruses containing mutations in the 2C-encoding region, which contributed to resistance to loxapine succinate. Analysis of molecular dynamics simulations of the interaction between 2C and loxapine suggested that loxapine binds to the N-terminal region of 2C, and that resistant mutations impede these interactions. We further demonstrated that administration of loxapine succinate to HAV-infected Ifnar1 -/- mice (which lack the type I interferon receptor) results in decreases in the levels of fecal HAV RNA and of intrahepatic HAV RNA at an early stage of infection. These findings suggest that HAV protein 2C is a potential target for antivirals, and provide novel insights into the development of drugs for the treatment of hepatitis A.